日本南極地域観測隊宇宙線部門船上観測結果報告 - 福島, 紳; フクシマ, シン; 小玉, 正弘; コダマ, マサヒロ; 牧野, 忠男; マキノ, タダオ; 宮崎, 友喜雄; ミヤザキ, ユキオ; FUKUSHIMA, Shin; KODAMA, Masahiro; MAKINO, Tadao; MIYAZAKI, Yukio (国立極地研究所, 1964)
P(論文) 第1次から第6次までの,南極観測船「宗谷」船上で行なった宇宙線強度の観測データの最終結果を集録した.地磁気緯度並びにdipole modelのcut off rigidityも同時に与えてある. Cosmic-ray intensities have been measured along a constant ship-route between Japan and the Antarctic, five times for the nucleonic component and three times for the meson component during 1956-62. Final results of the cosmic-ray data obtained are presented with descriptions of observational conditions in each survey and procedure of data reduction. departmental bulletin paper